ROLE OF FREEDOM OF EXPRESSION OF POLITICAL VIEWS AND BELIEFS IN THE FUNCTIONING OF A DEMOCRATIC POLITICAL - BAITALYUK, ZORYANA (Ehrlich’s Journal, 2024)
The article examines the role of freedom of expression of political views and beliefs in the functioning of a democratic political regime. It is stated that freedom of expression of political views and beliefs is a guarantee for the functioning of representative democracy, where the rights and freedoms of citizens are protected by legal mechanisms, and repressive influence by the government is prohibited. It is emphasized that freedom of expression is the foundation for building a democratic society free from censorship. The ability to express one’s thoughts and beliefs, challenge opposing political views, and criticize opponents without fear of persecution or retaliatory measures reflects the difference between living in a democratic country and living in a totalitarian state. Freedom of expression of political views and beliefs ensures the real implementation of the principles of multipartyism and ideological diversity, allowing citizens to exercise their political rights and make choices based on their own convictions. This freedom is an integral element of the functioning of civil society and the establishment of the rule of law. It has been emphasized that without a free press, without the free dissemination of information and ideas, without the right to access information, freedom to create information messages, and the freedom to use available communication channels for transmitting and spreading information, there can be no discussion of the existence of a rule of law state or a developed and stable civil society. It has been noted that the freedom of expression of political views and beliefs is the legal framework and foundation for the realization of other important civil and political human rights: the right to freedom of assembly and association, the right to freedom of speech, and the right to freedom of thought, conscience, and religion. It has been concluded that the freedom of expressing views and beliefs must be protected both in the interests of democratic processes in the state, for which it is decisive, and in the interests of the selfrealization of each individual as a person.